Scaling Properties of Universal Tetramers - Hadizadeh, M. R. [UNESP]; Yamashita, Marcelo Takeshi [UNESP]; Tomio, Lauro [UNESP]; Delfino, A.; Frederico, T. (Amer Physical Soc, 2011)
We evidence the existence of a universal correlation between the binding energies of successive four-boson bound states (tetramers), for large two-body scattering lengths (a), related to an additional scale not constrained by three-body Efimov physics. Relevant to ultracold atom experiments, the atom-trimer relaxation peaks for vertical bar a vertical bar -> infinity when the ratio between the tetramer and trimer energies is similar or equal to 4.6 and a new tetramer is formed. The new scale is also revealed for a < 0 by the prediction of a correlation between the positions of two successive peaks in the four-atom recombination process.